2015
DOI: 10.1123/japa.2012-0337
|View full text |Cite
|
Sign up to set email alerts
|

Aging Expectations are Associated With Physical Activity and Health Among Older Adults of Low Socioeconomic Status

Abstract: The purpose of the current study was to determine whether aging expectations (AE) are associated with physical activity participation and health among older adults of low socioeconomic status (SES). A cross-sectional analysis of a sample of 170 older adults (mean age 70.9 years) was conducted. Data on AE, physical activity, and health were collected using the 12 item Expectations Regarding Aging instrument, the Healthy Physical Activity Participation Questionnaire, and the Short Form-36, respectively. Adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…For instance, older adults with high expectations for aging were more likely to report a high level of physical activity than those with lower age expectations, even after controlling many other variables (e.g., age, gender, level of education, comorbidity). These results have been confirmed with older adults of low socioeconomic status [ 24 ]. It is worth noting that low expectations for aging are more detrimental to the adoption of appropriate health behaviors (e.g., physical activity) than the benefits of having high expectations for aging [ 25 ].…”
Section: Introductionsupporting
confidence: 56%
“…For instance, older adults with high expectations for aging were more likely to report a high level of physical activity than those with lower age expectations, even after controlling many other variables (e.g., age, gender, level of education, comorbidity). These results have been confirmed with older adults of low socioeconomic status [ 24 ]. It is worth noting that low expectations for aging are more detrimental to the adoption of appropriate health behaviors (e.g., physical activity) than the benefits of having high expectations for aging [ 25 ].…”
Section: Introductionsupporting
confidence: 56%
“…Although the administrative health region in which our study population was recruited is representative of urban, rural and metropolitan regions of the province [ 46 ], it is more likely that participants living close to primary care clinics may feel a greater sense of neighborhood security independent of deprivation. Dogra et al, (2015) also looked at the association between aging expectations and physical activity on HR-QOL in older adults with low socio-economic status and found that expectations regarding ageing were associated with physical activity and HR-QOL outcomes [ 47 ]. More research is needed on the gender specific associations between physical activity and health outcomes in older adults to better understand and discriminate between potential moderating and mediating psycho-social factors of this association.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The recent pilot work of using Tai Chi to intervene in low-income, ethnically diverse older community residents with complex chronic diseases has shown that Tai Chi is a potential intervention, because it is effective, does not require equipment and is flexible. [20][21][22][23][24] Partnering and collaborating with community-based organizations is essential to implementing and sustaining fall prevention programs. [5] To better understand the perspectives of older Arab American women regarding the feasibility of implementing a Tai Chi fall prevention program, the researchers teamed with Arab Community Center for Economic and Social Services (ACCESS) and developed a pilot Tai Chi exercise program for older Arab Americans through the use of multilingual and culturally sensitive strategies.…”
Section: Introductionmentioning
confidence: 99%